2004
DOI: 10.1097/01.wco.0000137530.68867.93
|View full text |Cite
|
Sign up to set email alerts
|

Falls in Parkinson's disease

Abstract: No dramatic breakthroughs have occurred during the review period, but new information in various areas may be useful for practising clinicians. Interesting new questions have been raised that should fuel studies of pathophysiological mechanisms, which could help in the development of improved treatment strategies to reduce falls in Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
155
0
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(170 citation statements)
references
References 60 publications
2
155
0
13
Order By: Relevance
“…In Parkinson's disease (PD), the most disabling symptoms involve gait and balance problems. Major clinical significance has been attributed to the falls suffered by PD patients, which are caused by independent, but coexisting, mechanisms: balance instability, difficulties with transfers (change in position), gait changes and orthostatic syncope 7 . Treatment is based on drug therapy, neurosurgery and physical therapy, but none of these options is efficient when used alone.…”
Section: Introductionmentioning
confidence: 99%
“…In Parkinson's disease (PD), the most disabling symptoms involve gait and balance problems. Major clinical significance has been attributed to the falls suffered by PD patients, which are caused by independent, but coexisting, mechanisms: balance instability, difficulties with transfers (change in position), gait changes and orthostatic syncope 7 . Treatment is based on drug therapy, neurosurgery and physical therapy, but none of these options is efficient when used alone.…”
Section: Introductionmentioning
confidence: 99%
“…Postural instability is one of the major symptoms of Parkinson's disease, and the instability in the control of upright stance and posture in PD often results in falling (Bloem et al, 2001;Wood et al, 2002;Grimbergen et al, 2004;Bloem et al, 2006). Several studies reported that postural sway patterns during quiet stance in PD patients are different compared to those of healthy elderly subjects, with PD patients displaying larger lateral excursion compared with anteroposterior excursion (Mitchell et al, 1995;Morris et al, 2000;Van Wegen et al, 2001; Van der Burg et al, 2006).…”
Section: Body Inclination During Sitting and In Relation To Falling Fmentioning
confidence: 99%
“…For example, individuals within this population often present with a gait pattern that is characterized by shortened step length and reduced velocity. As the disease progresses, gait impairments worsen and individuals may develop a festinating gait pattern with short, rapid steps, or freezing of gait, which may lead to falls and decreased quality of life (Grimbergen, Munneke, & Bloem, 2004;Shulman, 2010;Shulman et al, 2008).…”
mentioning
confidence: 99%